Obstacles to Co-Operation in the Framework Programme - Švarc, Jadranka; Lažnjak, Jasminka; Perković, Juraj (2014)
Researchers from WBC significantly lag behind researchers from EU member states in both intensity of research cooperation and in research mobility. Participation in FP is of critical importance for each country in the regions since research programmes and funding of FP dictate the dynamic and direction of research trajectories of all countries in the region. The most significant barriers to cooperation of researchers from WBC in FP are the Lack of the Project Management Capacities and the EC Bureaucratic barriers. It illustrates that capacity building to administer and to manage projects according to the rules and procedures of the EC is the most critical part of cooperation. The level of national investments in research (between 0.15% and 0.77% of GDP) is insufficient to enable WBC to compete in FP on equal footing with the member states. The different policy measures should be applied to improve the international cooperation of WBC on national and particularly on the regional level
ENG